ANALISIS FAKTOR YANG MEMENGARUHI PENGGUNAAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) PADA WANITA PUS DI WILAYAH KERJA PUSKESMAS KAWUA KABUPATEN POSO - Rualemba, Novi Krisanti; Rifai, Muhammad; Azis, Rahmawati (Bina Generasi : Jurnal Kesehatan, 2025)
The government's efforts to enhance community welfare through the Family Planning Program (KB) and the promotion of Long-Term Contraceptive Methods (MKJP) still encountered significant challenges. Despite targeting couples of reproductive age (PUS) as the primary beneficiaries of these programs, the uptake of MKJP remains below the desired levels. Various factors influence the decision-making process of these couples, including their knowledge about MKJP, perceptions of its efficacy, family support, sociocultural norms, and the role of healthcare workers. This study employed an analytical survey method with a Cross-Sectional Study design to assess the impact of these variables on the decision of PUS within the Kawua Community Health Center area to adopt MKJP. 90 couples of reproductive ages involved in this study, selected from 876 of total population through proportional sampling technique. The findings indicate that four out of the five examined factors significantly influence the use of MKJP in this population, they are knowledge about MKJP, perceptions of its efficacy, family support and the role of healthcare workers. The sociocultural norms was not significantly affective to decision of MKJP usage. To improve MKJP adoption, it is recommended that authorities enhance the knowledge of PUS about long-term contraceptive methods, thereby fostering more positive perceptions. Additionally, involving family members, particularly husbands, in counseling sessions about MKJP could be beneficial. Furthermore, improving the knowledge and skills of healthcare workers and providing better healthcare facilities are crucial steps in supporting the successful implementation of MKJP.